The Regional Western Sweden SOM Survey 2007 - SOM Institute, University of Gothenburg (University of Gothenburg, 2009)
Western SOM has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Detta är den femtonde studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningen genomfördes med två olika enkätformulär: ett riktat till invånarna i Göteborg med kranskommuner och ett till dem hemmahörande i resterande delar av Västra Götaland. Enkätformulären innehåller till största delen gemensamma frågor. Några frågor är dock enbart ställda i en av de två enkäterna; framför allt handlar det om frågor enbart ställda i formuläret till invånarna i Göteborgsregionen. Båda enkäterna innehåller frågeområdena: Nyheter och dagstidningar; Politik och samhälle; Samhälle och service; Medier och samhälle; Trafik; Teknikinnehav och internet; Aktiviteter och fritidsvanor; Arbetsliv; och Om dig själv. Göteborgsregionens enkät innehöll även frågeområdena: Göteborg; Trygghet och säkerhet; samt Göteborgs-Posten.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 2007
Väst-SOM 2007
Keywords: culture; kultur; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; information and communications technology; informations- och kommunikationsteknologi; newspaper readership; tidnings läsekrets; public transport; kollektivtrafik; radio; radio; medical care; sjukvård; radio news; radionyheter; television channels; tv-kanaler; news; nyheter; television news; tv-nyheter; political participation; politiskt deltagande; government; regering; internet; internet; information retrieval; informationssökning; democracy; demokrati; internal politics; inrikespolitik; leisure time activities; fritidsaktiviteter; commuting; pendling; refugees; flyktingar; personal safety; personlig trygghet; reading (activity); läsande; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap